Common mental disorders among health care students Transtornos mentais comuns em estudantes da área de saúde - Vera Lúcia Dutra Facundes; Ana Bernarda Ludermir (Brazilian Journal of Psychiatry, 2005)
OBJECTIVES: This study aimed to determine the prevalence of common mental disorders (CMDs) among the population of graduate students in Physical Education, Nursing, Dentistry and Medicine at the University of Pernambuco, as well as to analyze the relationship between CMDs and some characteristics of the teaching-learning process. METHODS: A cross-sectional study was carried out in the second semester of 2001 involving all students in the second and sixth semesters of each course. A total of 443 students responded to two self-reporting questionnaires: the Self Reporting Questionnaire-SRQ-20 and another questionnaire regarding characteristics of the teaching-learning process. RESULTS: The overall prevalence of CMDs was 34.1% and was significantly higher among students who felt overloaded (OR = 2.67; 95% CI = 1.6-4.5) or reported special situations during childhood and adolescence (OR = 2.55; 95% CI = 1.5-4.4). CONCLUSION: These findings can serve as the basis for development of programs of disease prevention and student mental health care, as well as collaborating with reflections on the teaching-learning processes in university courses. OBJETIVOS: O estudo objetivou determinar a prevalência de Transtornos mentais comuns (TMC) na população de estudantes dos cursos de graduação em Educação Física, Enfermagem, Odontologia e Medicina, da Universidade de Pernambuco, e analisar a sua associação com algumas características do processo ensino-aprendizagem. MÉTODOS: Um estudo transversal foi conduzido, no 2º semestre de 2001, com todos os estudantes dos 2º e 6º períodos de cada um dos cursos envolvidos. Um total de 443 alunos respondeu ao Self Reporting Questionnaire-SRQ-20 e a um questionário sobre as características do processo ensino-aprendizagem. RESULTADOS: A prevalência total dos transtornos mentais comuns foi de 34,1%, sendo significativamente maior entre os que se sentiam sobrecarregados (OR = 2,67 IC95% 1,6-4,5) e os que afirmaram a presença de situações especiais durante a infância e adolescência (OR = 2,55 IC95% 1,5-4,4). CONCLUSÃO: Estes resultados são importantes para subsidiar ações voltadas para a prevenção e o cuidado com a saúde mental dos estudantes, assim como para colaborar com reflexões acerca do processo ensino-aprendizagem nos cursos universitários.